Indoor air particulate matter exposure of commuter bus passengers in Istanbul, Turkey - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2017)
Commuter buses are in very common use in Istanbul, the most crowded city in Turkey, for inner city passenger transportation. People in commuter buses are prone to substances mainly originated from traffic related activities on streets. Scientific studies indicate that air pollutants create problems on respiratory and cardiovascular health. The objective of this study was to determine particulate matter (PM) mass concentrations and their elemental compositions in indoor air environments of commuter buses serving in Istanbul. In this context, two commuter bus lines that can represent the general traffic density in Istanbul were selected as study location. Indoor air PM10 and PM2.5 samplings were performed in the buses serving on these lines under routine traffic conditions and while passengers were in the buses. Measurements indicated that the concentrations were well above the guidelines values given by the WHO and European air quality standards while they were below the short term and above the long term guidelines values of Air Quality Directives of Turkey at the time of the measurements. The measured elemental concentrations were below the limit value for Pb and target values for As, Cd, and Ni given by the European Air Quality Standards for Total Suspended Particulates (TSP). Results obtained for old technology commuter buses emphasize the benefits of air conditioned and tightly isolated new buses for better indoor air quality on PM concentrations.
Keywords: Traffic; PM10; PM2.5; Commuter bus; Indoor air; Heavy metals; PUBLIC TRANSPORTATION MODES; PERSONAL EXPOSURE; CARBON-MONOXIDE; HEALTH IMPACT; MEXICO-CITY; AMBIENT AIR; PM2.5; POLLUTION; MICROENVIRONMENTS; OUTDOOR